Determination of the charge transport delay time during the smelting of manganese alloys in high-power ferroalloy electric furnaces - Gladkikh , V.A.; Ruban , A.V.; Kuzmenko , S.M.; Riabtsev, O.O.; Anosov , O.V.; Kravchenko , V.P. (Theory and Practice of Metallurgy, 2024)
Improvement of technical and economic indicators of the smelting process of ferroalloys occurs by solving issues of operational control of technological processes, and their optimization is associated with the use of reliable practical initial data. Therefore, in the work, in order to establish correlations between the initial parameters and final indicators, taking into account the technological inertia of the process, an adjusted "transport delay" method is proposed. The "transport delay" time of the RPZ-63 electric furnace was experimentally determined. The practical significance of the results lies in obtaining more reliable industrial data on the dependence of the influence of the electrode resistance on the furnace productivity, specific electrical energy consumption and the manganese extraction coefficient in the alloy.